ANALISIS VALIDITAS ISI PADA INSTRUMEN PENILAIAN AKHIR SEMESTER MATA PELAJARAN IPAS DI SD - Syafitri, Anis; Anggraini, Dini Puji; Parinduri, Wina Mariana; Rambe, Titin Rahmayanti; Rambe, Nurhamimah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
This research aims to analyze the content validity of instruments used at schools. In this research, content validity is measured from three aspects, namely material, construct, and language/culture/ethics aspects. The method used in this research uses quantitative descriptive methods. Content validity was assessed by 8 validators by filling a questionnaire. The results obtained from the validator are then analyzed by calculating the Aiken's V index. The Aiken's V value is used to ensure that the instrument used meets the content validity criteria and is categorized as suitable for use as a measuring tool. Based on analysis using Aiken's V, the averages obtained for the material, construct, and language/culture/ethics aspects were respectively in the very high, very high, and high categories. And overall the content validity of the instruments used in schools has met good content validity standards in the very high category. However, determining the criteria for a good assessment instrument is not only content validity, but also construct validity, empirical or item validity, and reliability. So, to further ensure that the quality of the end-of-semester assessment instruments used in schools is categorized as fully adequate, further research can be carried out by future researchers.